2003
DOI: 10.1111/j.1572-0241.2003.07424.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Mucosa-Associated Lymphoid Tissue Lymphoma

Abstract: The connection between Helicobacter pylori and gastric mucosa-associated lymphoid tissue (MALT) lymphoma is well established. H. pylori infection causes an immunological response, leading to chronic gastritis with formation of lymphoid follicles within the stomach. These lymphoid follicles resemble nodal tissues found throughout the body and are composed of reactive T cells and activated plasmal cells and B cells. The B cells are responsible for initiating a clonal expansion of centrocyte-like cells that form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 80 publications
2
78
0
1
Order By: Relevance
“…However, primary gastric lymphoma is the most common extranodal lymphoma (1)(2)(3)(4)(5). Histological features of gastric low-grade lymphomas closely resemble mucosa-associated lymphoid tissue (MALT) (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, primary gastric lymphoma is the most common extranodal lymphoma (1)(2)(3)(4)(5). Histological features of gastric low-grade lymphomas closely resemble mucosa-associated lymphoid tissue (MALT) (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that the prevalence of infection depends on the lymphoma's histological grade or the diagnostic method used, among others (8). A knowledge of the true prevalence of H. pylori in patients with MALT lymphoma is clinically relevant, as the detection of this organism will be followed by adequate eradication treatment, with consequent tumor regression in a high number of cases (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Since the successful isolation of Helicobacter pylori in 1984 by Marshall and Warren (19), H. pylori infection has been recognized to have a causal role in peptic ulcer disease and a strong association with gastric carcinoma (1,8). H. pylori characteristically displays a great genetic variability due to a high rate of spontaneous mutations and genetic recombination (6,9,23).…”
mentioning
confidence: 99%
“…Once acquired, H. pylori may persist throughout the life of the human host in the absence of appropriate antibiotic treatment. Persistent H. pylori colonization can lead to the development of peptic ulcers, gastritis, mucosa-associated lymphoid tissue, lymphoma, and gastric cancer (1,11). Current first-line eradication therapies involve a proton pump inhibitor or ranitidine bismuth citrate and two antibiotics, clarithromycin and either amoxicillin or metronidazole.…”
mentioning
confidence: 99%